Analysis Of Women's Perception of the Effectiveness of Gender-Based Violence Protection Policies in Balikpapan (JED (Jurnal Etika Demokrasi), 2025)
Gender-based violence remains pervasive in Indonesia, yet the practical effectiveness of protection policies at the local level is not well understood. This study aims to analyze women’s perceptions of the effectiveness of gender-based violence protection policies in Balikpapan by exploring how the regulatory framework is experienced in practice, what barriers hinder access to services, and how local government and community actors shape policy implementation. Employing a qualitative descriptive design, the research draws on in-depth interviews, non-participant observations, and document analysis to capture institutional dynamics and lived experiences across relevant service and governance settings. The findings show that, although policies such as the establishment of the UPTD PPA and related mechanisms provide a formal structure for protection, their perceived effectiveness is significantly constrained by structural limitations, entrenched cultural stigma, psychological trauma, and institutional inefficiencies. Simultaneously, the collaborative engagement of local government, community cadres, and civil society organizations illustrates the critical role of shared governance in enhancing accessibility, legitimacy, and trust in protection services. The study concludes that meaningful protection cannot be secured by legal frameworks alone but requires an inclusive, responsive, and context-sensitive implementation strategy that addresses systemic and socio-cultural obstacles. The novelty of this research lies in integrating women’s perceptions, multi-level barriers, and governance configurations within a single analytical framework. It contributes empirically and conceptually to debates on localized gender-based violence governance and offers actionable insights for strengthening community-embedded protection systems in comparable urban settings